ANALISA KEBAHASAAN SEBAGAI METODE ISTINBAT HUKUM ISLAM DARI TEKS AL-QUR'AN (STUDI ANALISIS HERMENUTIKA HUKUM ATAS PEMIKIRAN AL-SUBKI DALAM KITAB JAM'U AL-JAWAMI') - Khoirul Anwar; Nihayatut Tasliyah (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2022)
As the main Islamic law, the Qur'an needs a reading approach in order to reveal the relevant meaning in accordance with the times. Al-Subki, as one of the leading scholars in the Shafi'iyah madhhab describes the method of interpreting the text of the Qur'an in his book Jam'u al-Jawami'. This book is quite popular among the santri, but not much has been revealed about the theories described in it as an effort to deal with the changes and developments of the times. This study describes a model of interpretation or hermeneutics with an ushuli pattern as an effort to explore the law from the holy text of the Qur'an.